Paradoxes and partnerships: a study of knowledge exploration and exploitation in international development programmes - Lannon, John; Walsh, John N. (Journal of Knowledge Management, 2019)
Purpose – This paper aims to look at how organisational partnerships balance knowledge exploration and exploitation in contexts that are rife with paradoxes. It draws on paradox theory to examine the partnership’s response to the explore-exploit relationship.

Failing Forward: How CARE is focusing on what goes wrong to improve impact - Janoch, Emily (2019 CLA Case Competition, 2019)
CARE's Failing Forward initiative is sparking opportunities to showcase the ideas that don't work so we can spend more time implementing the ones that do. It's changing the conversation inside the organization, and leading to changes in the way we design and implement programs. It's also allowing us to make connections across a global portfolio of more than 900 projects, and with new and different partners to learn from their experience.